Development of the Virtual Taekwondo Training Environment Prototype for Self-Directed Taekwondo Training - Mohd Jelani, Nur Ain; Zulkifli, Abdul Nasir; Ismail, Salina; Yusoff, Mohd Fitri (Universiti Teknikal Malaysia Melaka, 2018)
Taekwondo is a martial art that has been practised by over 50 million people all over the world, and this number is increasing which makes Taekwondo more popular.Normally, Taekwondo training is conducted in a hall or large open spaces in the presence of a trainer.However, this approach has some limitations in supporting self-directed training.Even though there are several supplementary materials for Taekwondo training, they have many limitations.This paper introduces Virtual Reality and Motion Capture technologies as an alternative to the existing Taekwondo training approaches.The main advantage of these technologies for self-directed training is that they are able to imitate the trainer’s movement and provide three-dimensional displays of body movements which can be viewed from any angles. This enables the trainees to understand and follow the movements without assistance from the real trainer. This paper presents the design and development of the Virtual Taekwondo Training prototype as supplementary material for self-directed Taekwondo training based on Virtual Reality and Motion Capture technologies.This prototype aims to provide a new approach to supplementary material that can provide trainees’ satisfaction while doing selfdirected Taekwondo training.